118. High frequency paired associative stimulation modulates the corticospinal excitability in human subjects: An EEG study. Issue 1 (January 2015) - Naro, A.; Russo, M.; Abdelkader, M.; Marino, M.; Morgante, F.; Rizzo, V.; Girlanda, P.; Quartarone, A.
<x xml:space="preserve">Abstract</x> To evaluate the effects of a brief PAS on the corticospinal excitability on M1, observing the modulation of the MEP amplitude and of the absolute EEG-power, and their correlations, as expression of cortical synaptic strengthening/weakening. We tested on 12 healthy subjects the effect of three PAS conditioning protocols (25 ms, 15 ms and sham ISI) on the MEP amplitude and the absolute EEG-power, and their specific correlations, 30' after the end of the protocols. We found after PAS25ms a MEP amplitude increase correlated to a global reduction in α/β-EEGpower and increase in θ/δ. After PAS15ms a MEP amplitude decrease correlated to a global increase in α/β-EEGpower and reduction in θ/δ. No changes were found after rPASsham. Looking at these modulations and correlations, it is conceivable that the effects of PAS25ms could be expression of cortical synaptic potentiation. On the contrary the effects of PAS15ms could mean cortical reset. The modulation could be dependent from cortical GABAergic, glutamatergic and cholinergic circuitries. Beyond the purely neurophysiological aspects, our protocol could be interesting in neuro-rehabilitation, taking account of the effective, quick and persistent modulation of cortical oscillatory activity at bi-hemispheric level.